Potential for naturalising the concrete-lined storm channels in Singapore - Tay, Sharon Xue Ren. (2009)
The objective of this report is to investigate the potential of naturalizing concrete-lined storm channels in Singapore. Two techniques, bioretention basin and swale, recommended for sustainable drainage system (SUDS) are considered to naturalize concrete-lined storm channels. The existing concrete-lined storm channels are already designed to meet the hydraulic requirements; therefore, the limited geometric dimensions of the channels posed a difficulty to naturalize the storm channels. The change in roughness coefficient of the storm channel has to be taken into consideration, as any misinterpreted value will have adverse effects on the capability of the storm channel to serve as a catchment area. In addition, the high capital costs, designing and maintenance efforts required for implementing bioretention and swales posed as a problem to naturalized concrete-lined storm channels. However, it has to be taken into the account that these costs outweigh the benefits that naturalizing concrete-lined storm channels bring about. It is more than just providing an environment of high aesthetic value to the community; it also helps improve the quality of storm water that is retained and lessen the quantity of runoff. With the substantial incorporation of SUDS techniques into local concrete-lined storm channels, the supply of water form our local catchment areas will be considerable. These benefits that arise from the naturalizing of concrete-lined storm channels proved to be worthwhile for overcoming the difficulties of incorporating SUDS techniques. There is a definite potential in naturalizing concrete-lined storm channels, given the fact that many cities including Singapore have successfully introduced naturalized storm channels in the community.